Gamification in Education Management : Fulfilling Students’ Intrinsic Needs and Learning Outcomes - Alvi, Irum (Prabandhan: Indian Journal of Management, 2024)
Purpose : Education management is essential to utilizing technology’s potential to revolutionize the educational process, which calls for more investigation into the systems that support students’ learning objectives and basic needs. The research investigated the ways in which education administration might use technology to address students’ basic needs and improve learning results. Based on the self-determination theory (SDT), the research examined the role of gamification elements in learning applications as a means to fulfill students’ needs for competence, autonomy, and relatedness. Methodology : The study collected data through an online survey using convenience sampling from 144 professional students (117 males and 27 females). The hypotheses were tested using partial least squares structural equation modeling with SmartPLS v3.2.9 to analyze the impact of gamification on students’ needs and learning outcomes. Findings : The study found that gamified experiences that included social presence, challenge, achievement, personalization, identification, and encouragement had a favorable and significant impact on students’ basic requirements for relatedness, competence, and autonomy. The fulfillment of the needs for competence and relatedness influenced the sense of learning outcome attainment. However, the fulfillment of the need for autonomy influenced the sense of learning outcome attainment positively, yet insignificantly. Additionally, the achievement of learning outcomes influenced students’ intent to use learning apps. Practical Implications : The study provided valuable insights for educational management on effectively implementing gamification strategies to fulfill students’ intrinsic needs and enhance learning outcomes. Originality/Value : The study contributed to the academic discourse by integrating SDT with gamification in educational management, offering a novel perspective on how technology-driven strategies can meet students’ intrinsic needs and improve learning outcomes.